The institution of environmental reporting in Japan: an exploratory study / Afdal Madein - Madein, Afdal (Accounting Research Institute (ARI), 2020)
Although Japan has been having a high environmental reporting rate for a long time, the contextual factors promoting it are limitedly explored. Investigating them could enrich references to understand the improvement of this practice. Therefore, this study aimed to explore the contextual factors promoting this practice in Japan based on the Institutional Theory by applying thematic analysis to several official documents from the Japanese government. The analysis discovered regulative, normative, and cognitive elements emanating from regulations and initiatives from the Government, Japanese society and companies, and overseas practices, which promote environmental reporting as a tatemae. The findings provide a basic understanding of institutional elements endorsing environmental reporting in Japan to feed future research and other countries in improving this practice.